Prevalence and correlates of substance use among psychiatric inpatients. Issue 2 (24th February 2017) - Hamdan‐Mansour, Ayman M.; Al‐Sagarat, Ahmad Y.; AL‐Sarayreh, Faris; Nawafleh, Hani; Arabiat, Diana H.
Abstract: Purpose: This study aimed at examining correlates of substance use among patients diagnosed with psychiatric disorders in Jordan. Methods: This study used a nonexperimental descriptive survey design. Data were collected through using DUSI–R scale obtained through a self‐designed questionnaire. A total of (203) subjects satisfied the inclusion criteria. Results: Most used substances prior to admission were caffeine (78.2%), cigarette (60.9%), and alcohol (22.2%), while the least were heroin (1.2%) and inhalants (0.08%). Patients diagnosed with schizophrenia had higher percentages among all other disorders ( n = 16, 21.9%), although there was no statistical difference among patients related to their psychiatric disorders. Conclusion: We recommend that mental health professionals be equipped with necessary skills to manage substance use among patients with psychiatric disorders.